Moving Beyond Viral Suppression: Poor Patient–Provider Communication and Its Impact on Healthcare Outcomes Among People Living With HIV in the United States - Bekana K. Tadese MPH, PhD; M. Janelle Cambron-Mellott PhD; Jean Marie Arduino ScD, MS; Bridget L. Balkaran MPH; Shakiba Eslamimehr PhD; José M. Zuniga PhD, MPH (Journal of the International Association of Providers of AIDS Care, 2025)
Background While advancement in treatment have turned HIV into a manageable chronic condition achieving viral suppression, it has become imperative to focus on overall health and improving health-related quality of life of people living with HIV (PLHIV) beyond viral suppression. This study aimed to describe how PLHIV perceive and manage their overall health, factors influencing patient–provider communication, and the impact of poor patient–provider communication on health outcomes. Methods This cross-sectional, online survey recruited HIV-positive adults in the United States between February 22 and June 2, 2022, via the Profiles Panel. Data on sociodemographic and health characteristics, and social determinants of health were collected. The study assessed how PLHIV view and manage their overall health by measuring self-rated overall health, Patient Activation Measure ® (PAM ® ), general and HIV-specific health locus of control (HLOC). Multivariable analyses were used to identify the barriers and unmet needs in the patient–primary HIV clinician communication. Results Of the 781 PLHIV who completed the study, most participants were cisgender male (56.2%), non-Hispanic, White (51.5%), and <50 years old (67.0%). Over 90% of participants reported being virally suppressed or having an undetectable viral load. About one-third (31.5%) reported their overall health as either poor or fair. Participants were highly activated in managing their health with 58.0% at PAM level 3 and 33.3% at level 4 and had high scores across the dimensions of both general and HIV-specific HLOC. Overall, 18.2% of the participants reported suboptimal satisfaction and 16.8% reported facing difficulty in verbalizing their HIV-related health concerns with their primary HIV clinician. One-fourth of the participants reported “sometimes” or “never/rarely” discussing their HIV treatment medications with their primary HIV clinician. Furthermore, participants dissatisfied with their primary HIV clinician were twice as likely to self-report poor overall health (OR: 2.2, 95% CI: 1.38, 3.48). Conclusion This study underscores the critical role of managing overall health by optimizing patient–provider relationships in influencing individual holistic well-being beyond viral suppression. Healthcare interventions should prioritize strategies to enhance patient communication and satisfaction, recognizing its profound impact on HIV and overall health outcomes.